2011
DOI: 10.1111/j.1945-5100.2011.01218.x
|View full text |Cite
|
Sign up to set email alerts
|

Nickel abundance in stony cosmic spherules: Constraining precursor material and formation mechanisms

Abstract: Abstract-We report bulk and olivine compositions in 66 stony cosmic spherules (Na 2 O < 0.76 wt%), 200-800 lm in size, from the Transantarctic Mountains, Antarctica. In porphyritic cosmic spherules, relict olivines that survived atmospheric entry heating are always Ni-poor and similar in composition to the olivines in carbonaceous or unequilibrated ordinary chondrites (18 spherules), and equilibrated ordinary chondrites (one spherule). This is consistent with selective survival of high temperature, Mg-rich oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 75 publications
(201 reference statements)
3
35
0
Order By: Relevance
“…below detection limit) and low SiO 2 contents (<52 wt.%). Thus, they differ from the terrestrial glass particles found in the micrometeorite traps, volcanic glass shards (Na 2 O >3 wt.%; Curzio et al, 2008) or microtektites (SiO 2 >59 wt.%; Folco et al, 2009), and from ablation debris spherules (Na 2 O $2 wt.%; Genge and Grady, 1999;van Ginneken et al, 2010;Cordier et al, 2011c). Therefore, all the studied particles can be classified as cosmic spherules.…”
Section: Resultsmentioning
confidence: 95%
“…below detection limit) and low SiO 2 contents (<52 wt.%). Thus, they differ from the terrestrial glass particles found in the micrometeorite traps, volcanic glass shards (Na 2 O >3 wt.%; Curzio et al, 2008) or microtektites (SiO 2 >59 wt.%; Folco et al, 2009), and from ablation debris spherules (Na 2 O $2 wt.%; Genge and Grady, 1999;van Ginneken et al, 2010;Cordier et al, 2011c). Therefore, all the studied particles can be classified as cosmic spherules.…”
Section: Resultsmentioning
confidence: 95%
“…In the chondrule formation processes, crystallographic constrain at crystal growth occur in barred olivine and radial pyroxene chondrules. Barred olivine texture is also reported in cosmic spherules, which are melted micrometeorite (Cordier et al, 2011). The fine particle falling apparatus developed in this study has expanded cooling rate in laboratory experiments up to 2 × 10 6 K/h.…”
Section: Discussionmentioning
confidence: 96%
“…Study of the composition of such spherules, in particular the Ni‐contents of their olivines, as shown by Cordier et al. (), together with vesicle contents should allow these two possibilities to be discriminated.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of large cosmic spherules (>200 μm) have been shown to have ordinary chondrite‐like precursors (Cordier et al. ), while the remainder are probably derived mainly from precursors similar to carbonaceous chondrites (Genge et al. ).…”
Section: Samples and Methodsmentioning
confidence: 99%
See 1 more Smart Citation